Topographic Maps of Brain Regions to Measure Human Trust in Automation - Oh, Seeung; Seong, Younho; Yi, Sun; Park, Sangsung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
As complex automation increasingly enters the workplace, a human operator’s trust affects the proper use of automation. This research aimed to identify stimulated brain regions using topographic maps to measure human trust in automation. Power spectrum analysis classified the frequency range, and coherence analysis identified functional connectivity within the brain regions. The results showed that the frontal lobe in the alpha and beta waves had strong connectivity in the trust situation. In contrast, the temporal lobe in the gamma waves had strong connectivity in the mistrust situation. These findings can contribute to monitoring human operators’ trust in automation in uncertain or urgent situations and designing complex automation by calibrating human trust consistent with the automation abilities in the industry.